Correction: Satisfaction with regular hospital foodservices and associated factors among adult patients in Wolaita zone, Ethiopia: A facility-based cross-sectional study. - Meskerem Teka; Gargi Dhar; Tadele Dana; Gedion Asnake; Negash Wakgari; Zeleke Bonger; Wakgari Binu Daga (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0264163.].